Value of real-time tissue elastography diffusion quantitative analysis combined with tumor markers for differential diagnosis of benign and malignant breast nodules - Zhu, Ling; Mei, Lina; Pan, Xuekui (Vojnosanitetski pregled, 2024)
Background/Aim. Serum tumor markers (TMs) are commonly combined with imaging examinations to differentiate benign and malignant breast nodules (BNs), but there are still limitations. The aim of the study was to determine the value of real-time tissue elastography (RTE) diffusion quantitative analysis combined with serum TMs for the differential diagnosis of benign and malignant BNs. Methods. A total of 149 patients with BNs were included in this study. They were assigned to the benign BN group (n = 87) and malignant BN group (n = 62). All patients were examined using RTE diffusion quantitative analysis. Venous blood was collected to detect the levels of TMs carcinoembryonic antigen-CAE, cancer antigen (CA) 153, and CA 199. The value of RTE diffusion quantitative analysis parameters, TMs, and their combination for the differentiation of benign and malignant BNs was analyzed using the receiver operating characteristic-ROC curve. Results. Among all the above indicators, the area ratio of the blue region (AREA%) had the highest differential value, with an area under the curve (AUC) of 0.916 [95% confidence interval (CI): 0.812–0.967], while sensitivity and specificity were 88.90% and 86.79%, respectively (p < 0.05). Compared to RTE diffusion quantitative analysis parameters or TMs alone, the combination of the two showed the highest value for the differentiation of benign and malignant BNs, with an AUC of 0.957 (95% CI: 0.834–0.982), while sensitivity and specificity were 95.50% and 94.33%, respectively (p < 0.05). Conclusion. RTE diffusion quantitative analysis combined with TMs has a high value for the differentiation of benign and malignant BNs.